'Don't look!' An online art therapy group for adolescents with Anorexia Nervosa. Issue 4 (1st October 2020) - Shaw, Lucy
ABSTRACT: Background: Delivering Art Psychotherapy online has become a necessary part of practice for many in 2020 due to the Covid-19 Pandemic. Art Psychotherapy practice and theory needs to be considered in light of this new way of working in addition to the impact on clients themselves. Context: This paper considers an experience of delivering online group Art Psychotherapy to adolescents attending an NHS day service programme for Anorexia Nervosa. A case vignette of three group sessions is provided to illustrate the process. The experiences and reflections of three clients are reported. Approach: The approach to the art therapy described is psychoanalytical as it focuses on importance of the relationship between the internal and external world and mentalization based as it aims to increase capacity to perceive and understand self and others. Outcome: It is argued that there are additional considerations for this client group when working online including body image concerns and experience of gaze. Conclusion: Consideration of the unique requirements of this client group are important when devising protocol for ways of delivering art therapy online. Implications for research: Further research could consider, on a larger scale, the perspectives of clients with eating disorders on having art therapy delivered online. Plain-language summary: This paper describes the set up and delivery of an online Art Psychotherapy group for adolescents with Anorexia Nervosa as part of an NHS day service. The group ran for seven weeks and was attended by three clients. I outline the theoretical framework of my approach to delivering this intervention. Theories of containment, gaze and joint attention are highlighted as being particularly relevant for working with this client group online. I describe the experiences of the clients who attended as well as my process as the art therapist. I note the main themes arising from this group as an intensified experience of gaze, body image concerns and a desire for control over what might be seen or shown. I reflect on my experience of feeling deskilled and having to alter my process to adjust to working online. I conclude that when working with this client group online these are important considerations to bear in mind. Future research is needed to gather perspectives from clients with eating disorders regarding their experience of art therapy being delivered online.